2001
DOI: 10.4049/jimmunol.167.10.6002
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G Inhibits Rolling Adhesion of Activated Human NK Cells on Porcine Endothelial Cells

Abstract: Human NK cells adhere to and lyse porcine endothelial cells (pEC) and therefore may contribute to the cell-mediated rejection of vascularized pig-to-human xenografts. Since MHC class I molecules inhibit the cytotoxic activity of NK cells, the expression of HLA genes in pEC has been proposed as a potential solution to overcome NK cell-mediated xenogeneic cytotoxicity. HLA-G, a minimally polymorphic HLA class I molecule that can inhibit a wide range of NK cells, is an especially attractive candidate for this pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 47 publications
1
71
0
Order By: Relevance
“…Human NK cells have further been reported to lyse porcine target cells in vitro, especially after activation and in the presence of human serum containing xenoreactive natural antibodies (27)(28)(29). This susceptibility of pEC to human NK cytotoxicity may be explained by the failure of swine leukocyte antigen (SLA) class I molecules to interact with human NK inhibitory receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Human NK cells have further been reported to lyse porcine target cells in vitro, especially after activation and in the presence of human serum containing xenoreactive natural antibodies (27)(28)(29). This susceptibility of pEC to human NK cytotoxicity may be explained by the failure of swine leukocyte antigen (SLA) class I molecules to interact with human NK inhibitory receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Of interest, an association between HLA-G polymorphisms and other chronic inflammatory disorders, such as inflammatory bowel disease (33,34), asthma (35,36) and multiple sclerosis (37)(38)(39), has been repeatedly reported. Besides the potential role played by HLA-G in inflammation and immunity (15), there is evidence to suggest that this molecule may also modulate endothelial cell activity (40,41). In this regard, it has been previously demonstrated that purified recombinant soluble HLA-G is capable of downregulating endothelial cell proliferation and migration in vitro (42).…”
Section: Discussionmentioning
confidence: 99%
“…Forte et al (24,25) have shown that expression of HLA-G at the surface of PEC monolayers inhibits the rolling adhesion of activated human NK cells. In these experiments, rolling adhesion of activated NK cell lines to HLA-G transfected PEC monolayers was inhibited by 50% as compared with their rolling adhesion to nontransfected PEC.…”
Section: Hla-g Might Protect Allografts In Vivomentioning
confidence: 99%
“…Briefly, transfection of HLA-G1 cDNA or genomic HLA-G DNA into PEC or Chinese Hamster ovarian cells (CHO) lead to a 'partial' to complete inhibition (ranging from 30% to 100%) of the cytolytic function of human polyclonal NK cells and that of most human NK cell lines (22)(23)(24)(25)(26). Furthermore, two studies showed a correlation between the level of HLA-G1 cell surface expression by transfected PEC and the extent of NK functional inhibition (25,26). The HLA-G receptors primarily involved in this inhibition remain unknown; however, while working with NK clones, Forte et al found no correlation between the ability of HLA-G-transfected PEC to inhibit NK lysis and the expression by the NK clones of the HLA-G receptor ILT2.…”
Section: Hla-g Might Protect Allografts In Vivomentioning
confidence: 99%
See 1 more Smart Citation